The holotype of Chenopodium baryosmon (Chenopodiaceae) rediscovered: just one of many type specimens from the private herbarium of Schultes, now in the Turczaninow herbarium at KW - Mosyakin, Sergei L.; Esser, Hans-Joachim; Freitag, Helmut (Phytotaxa, 2018)
The holotype of Chenopodium baryosmon (Chenopodiaceae), described by Schultes in 1820 and now treated as a synonym of Caroxylon imbricatum, has been discovered in the historical Turczaninow herbarium at KW (National Herbarium of Ukraine, Kyiv). The lectotype designation by Botschantzev (1975) is thus superseded following Art. 9.19 of the ICN. The specimen is discussed and illustrated, and information on isotypes is updated. This specimen is evidently one of many previously missing types from the private herbarium of Schultes, which was sold to Turczaninow in the 1853 and is now part of KW. Brief information about the Turczaninow herbarium and its expected holdings of Schultes’ specimens is provided.